Bitter leaf extract modulates antioxidant enzymes, immunoglobulins, organ weights, meat oxidation, and hepatic stress markers in broiler chickens exposed to aflatoxin B1 - Oloruntola, Olugbenga David (Holistic: Journal of Tropical Agriculture Sciences, 2026)
Background: This study examined the effects of bitter leaf extract on the oxidative enzymes, stress markers, immunoglobulins, organ weights, meat oxidation, and liver health in broiler chickens exposed to aflatoxin-B1. Methods: 240 day-old mixed-sex Cobb-500 broiler chickens were randomly assigned to the following treatment groups: CONT (Control); BE0AF (0.5 mg/kg aflatoxin-B1); BE1AF (0.5 mg/kg aflatoxin B1 + 1 g bitter leaf powder/ L H2O)  or BE2AF (0.5mg/kg aflatoxin-B1 + 2 g bitter leaf powder/ L H2O), each with 60 chickens (6 replicates of 10 chickens). Findings: BE0AF significantly (P<0.05) lowered the serum superoxide dismutase (SOD) and higher malondialdehyde (MDA) levels compared to untreated chickens.  BE2AF resulted in similar MDA levels compared to chickens in the BE1AF and CONT groups. BE0AF group showed higher (P<0.05) lactate dehydrogenase (LDH) and lower catalase and glutathione peroxidase (GPx) levels than other groups. Immunoglobulin G levels were notably (P<0.05) lower in the BE0AF group, while immunoglobulins M and A were significantly (P<0.05) lower compared to the BE3AF and BE2AF groups. Liver and spleen weights were higher in the aflatoxin group, and meat catalase was lower (P<0.05) in BE0AF. Lipid and protein oxidation were higher (P<0.05) in BE0AF compared to CONT. Furthermore, liver HSP70, NF-κB, and LDH levels were higher (P<0.05) in BE0AF. Conclusion: Oral administration of bitter leaf extract of 1-2g/ L H2O bitter leaf powder mitigated oxidative stress and protected against aflatoxin-induced damage by improving various physiological markers in broiler chickens. Novelty/Originality of this article: This study was to assess the impact of bitter leaf aqueous extract on organ weights, immunoglobulin levels, serum biomarkers, meat oxidation, hepatic oxidative enzymes, and nuclear factor kappa B in broiler chickens exposed to AFB1.